A inovação social e as motivações de voluntários, na cidade de Joinville/SC, durante a pandemia de Covid-19 - Oliveira, Amanda Melchert da Silveira de (2023)
There are social challenges that neither the public nor the private sphere can solve independently; in these contexts, social innovation emerges as a possibility. From a space of experimentation for new solutions, social innovation projects can be developed by multiple actors with a focus on improving social well-being, and among them, the participation of volunteers stands out. Within this context, keeping volunteers motivated contributes to the intention of their continued involvement in project development. Objective: To understand the motivations of volunteers to develop social innovation projects during the Covid-19 pandemic in Joinville/SC. Method: Through a qualitative-quantitative approach, using the Volunteer Functions Inventory and semi-structured interviews with 16 volunteers who participated in the Agenda Saúde project, developed by Fab Lab Joinville for the Joinville City Hall, addressing Covid-19 scheduling solutions. Conclusion: This study contributed to understanding that the main motivations for this group of volunteers lie in the dimensions of Social/Enrichment and Values/Understanding. It also demonstrates that the pandemic had a significant impact on the decision to participate in this project.